The Qur'anic model of hospitality services and its application on Grand Putri Hotel of Kuala Terengganu - Mohammad Dhiya'ul Hafidh bin Fatah Yasin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The modern Islamic hospitality sector is witnessing new enhancements, especially in terms of the range of services and facilities offered. However, since room for improvement remains significant, this study aims to contribute to the sector by highlighting the hospitality characteristics that the Qur'an inspires to be the Qur'anic model of hospitality. In order to achieve this objective, the study adopted qualitative research in which data was collected through library research, individual interviews and observation. The most important finding is that the Qur'anic verses related to hospitality touch not only on the physical elements, but also the psychological principles. In particular, the latter, which should be given more priority, is about utilizing hospitality: to fulfil one's role as a servant and vicegerent of Allah on earth; to seek not only benefits for oneself, but also for the community and nation; and to aim for rewards in the afterlife without neglecting those of this earth. As example for the physical elements, they are vary. The story of Prophets Ibrahim and Sulaiman in entertaining their guests illuminates the elements of a welcoming banquet. Meanwhile, the description of the landscape attendants in Paradise inspires the meditators to design a hospitable landscape that pleases the human's intrinsic and extrinsic characteristics, as reflected in any impressive frontline hotel staff. In addition, the Qur'an also instructs adherents to learn from history; which among the most important lessons from Islamic history is waqf based hospitality establishments. The current study goes further by applying the findings of the library research on the operations of a modern Islamic hospitality hotel in order for it to become the benchmark. The Grand Puteri Hotel was chosen for this study because it is the best Islamic-branded hotel currently operating in Malaysia and its unique waqf. In its conclusion, the study recommends further developments of the Islamic hospitality sector, which centres on prioritizing seeking guidance from the Qur'an and referring to Grand Puteri Hotel as its benchmark. As for the stakeholders of the hotel, even though its performance is already revered, there are still elements to be improved.